2014
DOI: 10.1186/1471-2164-15-723
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Paenibacillus sabinae T27 provides insight into evolution, organization and functional elucidation of nif and nif-like genes

Abstract: BackgroundMost biological nitrogen fixation is catalyzed by the molybdenum nitrogenase. This enzyme is a complex which contains the MoFe protein encoded by nifDK and the Fe protein encoded by nifH. In addition to nifHDK, nifHDK-like genes were found in some Archaea and Firmicutes, but their function is unclear.ResultsWe sequenced the genome of Paenibacillus sabinae T27. A total of 4,793 open reading frames were predicted from its 5.27 Mb genome. The genome of P. sabinae T27 contains fifteen nitrogen fixation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…In this study, sequence analysis and RT-PCR demonstrated that the 10 genes nifB nifH nifD nifK nifE nifN nifX orf1 hesA nifV in P. graminis RSA19 were organized as an operon under the control of a -35/-10 type σ 70 -dependent promoter located upstream of nifB ( Figure 4 ). Similar results that the 10 genes nifB nifH nifD nifK nifE nifN nifX orf1 hesA nifV in P. sabinae T27 are organized as an operon were reported in [ 10 ]. In this study, qRT-PCR results showed that these 10 genes within the nif gene operon under N 2 -fixing condition (without NH 4 + and O 2 ) exhibited a significant transcript ranging from 60- to 1300-fold compared to non-N 2 -fixing condition (100 mM NH 4 + and 21% O 2 ) ( Figure 5 ), suggesting that nif gene expression in P. graminis RSA19 was strongly regulated by ammonium and oxygen.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, sequence analysis and RT-PCR demonstrated that the 10 genes nifB nifH nifD nifK nifE nifN nifX orf1 hesA nifV in P. graminis RSA19 were organized as an operon under the control of a -35/-10 type σ 70 -dependent promoter located upstream of nifB ( Figure 4 ). Similar results that the 10 genes nifB nifH nifD nifK nifE nifN nifX orf1 hesA nifV in P. sabinae T27 are organized as an operon were reported in [ 10 ]. In this study, qRT-PCR results showed that these 10 genes within the nif gene operon under N 2 -fixing condition (without NH 4 + and O 2 ) exhibited a significant transcript ranging from 60- to 1300-fold compared to non-N 2 -fixing condition (100 mM NH 4 + and 21% O 2 ) ( Figure 5 ), suggesting that nif gene expression in P. graminis RSA19 was strongly regulated by ammonium and oxygen.…”
Section: Resultssupporting
confidence: 86%
“…The orf1 located between nifX and hesA is the major pronounced difference in the nif cluster between Sub-group I and Sub-group II [8]. Each of the two nif gene clusters is organized as a single operon and transcribed under the σ 70 promoter located in front of nifB [9,10]. Recently, our studies have revealed that GlnR simultaneously acts as an activator and a repressor for nif gene transcription by binding to two different loci of the single nif promoter region according to nitrogen availability [11].…”
Section: Introductionmentioning
confidence: 99%
“…In most rhizobia, expression of genes related to secretion system, surface polysaccharides biosynthesis and RNS is needed for inducing nodule organogenesis and nodule development ( Putnoky et al, 1988 ; Lorkiewicz, 1997 ; Fauvart and Michiels, 2008 ; Li et al, 2014 ), and the type and/or number of these nodule-related genes are often play important roles in host specificity ( Horvath et al, 1986 ; Philip-Hollingsworth et al, 1989 ; Wang et al, 2014 ). Among our six tested strains, S. fredii USDA205 nodulated the same legume host (soybean) with B. diazoefficiens 113-2 and B. diazoefficiens USDA110 ( Table 1 ), while there were no genes related to secretion system, surface polysaccharides biosynthesis and RNS that were both specific and common to these three strains ( Figures 6 , 7 and Tables 4 , 5 ), suggesting that there was no gene specifically shared by rhizobia of different species to establish symbiosis with soybean, which was consistent with a previous study ( Tian et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our lab has completed genome sequencing of 13 nitrogen-fixing Paenibacillus spp., including P. polymyxa strains WLY78, TD94 and 1–43 and other nitrogen fixers of this genus 17 18 19 . We compared these strains to each other and to 18 other strains (2 N 2 -fixing strains and 16 non-N 2 -fixing strains) and revealed the heterogeneity, organization and evolution of the nitrogen fixation genes within the 31 genomes.…”
mentioning
confidence: 99%